Children with cerebral palsy: severity and trends over time. - Surman, G; Hemming, K; Platt, M; Parkes, J; Green, A; Hutton, J; Kurinczuk, J (2009)
Increasingly, more very-low-birthweight infants in the developed world are now expected to survive the neonatal period than was previously the case. There are concerns that there may be a related increase in the number of infants developing severe sensorimotor impairments. Pooled data from five registers contributing to the UK Network of Cerebral Palsy Registers, Surveys and Databases were used to identify patterns of motor impairment in relation to additional impairments and to birthweight, and to assess whether prevalence of cerebral palsy (CP) by birthweight and by severity of motor impairment had changed over time. Low-birthweight infants are at greater risk of developing CP than larger-birthweight babies. The CP rate amongst children with birthweights <2500 g was significantly higher at 16 per 1000 livebirths [95% confidence interval (CI) 14.9, 16.2] than 1.2 per 1000 livebirths [95% CI 11, 1.2] for normal-birthweight children. Despite being at greater risk of developing CP, smaller-birthweight babies are proportionately less likely to develop the most severe forms of motor impairment. Of those born weighing > or = 2500 g, 23% compared with 15% weighing <1000 g (P < 0.001) were in the most severely motor impaired group. Severe motor impairment is associated with higher levels of additional impairments. CP rates for each motor impairment group in the 1990s were similar to those in the late 1970s. Rates of CP among infants born below normal birthweight are high but have decreased over time. The CP rate for infants weighing 1000-1499 g at birth decreased from around 180 per 1000 livebirths in 1979 to around 50 per 1000 livebirths from the early 1990s onwards.